2001
DOI: 10.1007/bf02490362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isotopic dilution methods for determination of theophylline in the plasma and saliva of infants and children

Abstract: Isotope-dilution mass spectrometry (IDMS) using the direct inlet probe and an isotope dilution gas chromatographic-mass spectrometric (GC-IDMS) technique are presented for determination oftheophylline in paired specimens of plasma and saliva from infants and children treated with theophylline for idiopathic apnea of prematurity, or for asthma, lSN-theophylline was used as internal standard. A non-invasive means of individualization of the dosage was achieved by analysis of levels of the drug in saliva secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The S/P ratio of 1.24 in Khanna et al's study [23] was similar to the observations of others [33,34], while Toback et al [29] suggest the ratio to be closer to 1. Also, that found by Culea et al [31] is low, although they found the ratio to be higher in the infants than children. The lower correlations with unstimulated saliva which were seen by Siegel et al [30] were thought to be due to greater variability in the theophylline saliva concentration due to changes in flow rates and pH.…”
Section: Theophyllinementioning
confidence: 77%
See 4 more Smart Citations
“…The S/P ratio of 1.24 in Khanna et al's study [23] was similar to the observations of others [33,34], while Toback et al [29] suggest the ratio to be closer to 1. Also, that found by Culea et al [31] is low, although they found the ratio to be higher in the infants than children. The lower correlations with unstimulated saliva which were seen by Siegel et al [30] were thought to be due to greater variability in the theophylline saliva concentration due to changes in flow rates and pH.…”
Section: Theophyllinementioning
confidence: 77%
“…Also, that found by Culea et al . is low, although they found the ratio to be higher in the infants than children. The lower correlations with unstimulated saliva which were seen by Siegel et al .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations